Comparative analysis of physicochemical properties, bioequivalence, safety and tolerability of the first domestic semaglutide - A. S. Ametov; I. E. Shokhin; E. A. Rogozhina; T. G. Bodrova; M. E. Nevretdinova; P. A. Bely; K. Ya. Zaslavskaya; V. S. Scherbakova; D. V. Kurkin; K. N. Koryanova; E. S. Mishchenko; E. Yu. Kesova; et al. (Фармация и фармакология (Пятигорск))
Semaglutide is a representative of analogues of the incretin hormone human glucagon-like peptide-1 (GLP-1) and is currently used in Russia for the treatment of type 2 diabetes mellitus (T2DM; in monotherapy and in combination therapy), including patients with obesity and overweight.The aim of the work was to conduct a comparative assessment of the physicochemical properties, a biological activity, bioequivalence and safety, including tolerability and immunogenicity, of the drug Quincent® (semaglutide, 1.34 mg/ml, a solution for a subcutaneous administration, Promomed Rus LLC, Russia) and the drug Ozempic® (semaglutide, 1.34 mg/ml, a solution for a subcutaneous administration, Novo Nordisk A/S, Denmark) when administered to healthy volunteers.Materials and methods. To assess the degree of similarity of the study drug Quincenta® (semaglutide, 1.34 mg/ml, a solution for a subcutaneous administration, Promomed Rus LLC, Russia) with a chemically synthesized active substance to the original (reference) drug Ozempic® (semaglutide, 1.34 mg/ml, a solution for a subcutaneous administration, Novo Nordisk A/S, Denmark), a comparative study of physicochemical properties and a biological activity was carried out. To assess the bioequivalence of the study drug and the reference drug, an open randomized parallel comparative study with the participation of healthy volunteers (n=54), 54 participants of which had been included in the population, was conducted. The volunteers were randomized into 2 groups in a 1:1 ratio, and received a single dose subcutaneously either of the study drug (domestic semaglutide at a dose of 0.5 mg) or the reference drug (foreign semaglutide at a dose of 0.5 mg). The mode of administration was in the morning on an empty stomach. A semaglutide concentration was determined in serum samples using a previously validated enzyme-linked immunosorbent assay (ELISA) method. A quantitative determination of antibodies to semaglutide in the human serum by ELISA was carried out with a microplate photometer using ready-made kits pre-validated by the manufacturer. The conclusion about the bioequivalence of the compared drugs was made using an approach based on the assessment of 90% confidence intervals for the ratios of the geometric mean values of the parameters Cmax, AUC(0–t) of semaglutide in the measurement original units.Results. The results of the comparative analysis of the study drug and the reference drug demonstrate the comparability of their physicochemical properties and biological activity. The results of the clinical study demonstrated the bioequivalence of the test drug and the reference drug. Thus, the pharmacokinetic parameters of the drugs were comparable to each other: the Cmax value for the study drug was 42.088±8.827 ng/ml, for the reference drug Ozempic® it was 42.2556±7.84. Herewith, the half-life for the study drug and the reference drug was 168.39±39.47 and 157.99±28.57 hours, respectively. The resulting 90% confidence intervals for the ratio of the Cmax and AUC0–t values of the study drug and the reference drug were 90.89–109.15 and 91.66–111.27%, respectively. The tolerability of the drugs in the volunteers was notified as good. No adverse events were recorded during the study. No serious adverse events were reported throughout the study. According to the results of the immunogenicity analysis, no antibodies to Russian-made semaglutide were detected in the blood serum of the volunteers, which indicated the lack of Results. The results of a comparative analysis of the study drug and the reference drug demonstrate the comparability of physicochemical properties and biological activity. The results of the clinical study demonstrated the bioequivalence of the study drug and the reference drug. Thus, the pharmacokinetic parameters of the drugs were comparable to each other: the Cmax value for the study drug was 42.088±8.827 ng/ml, for the reference drug Ozempic® this figure was 42.2556±7.84. At the same time, the half-life for the study drug and the reference drug was 168.39±39.47 and 157.99±28.57 hours, respectively. The resulting 90% confidence intervals for the ratio of the Cmax and AUC0–t values of the study drug and the reference drug were 90.89–109.15 and 91.66–111.27%, respectively. Tolerability of the drugs in volunteers was noted as good. No adverse events were recorded during the study. No serious adverse events were reported throughout the study. According to the results of the immunogenicity analysis, no antibodies to Russian-made semaglutide were detected in the blood serum of the volunteers, which indicated the lack of the drug immunogenicity.Conclusion. In the course of the study, the comparability of the physicochemical properties and biological activity of the studied Russian drug with the chemically synthesized active substance Quincenta® to the reference drug Ozempic® was confirmed: the activity range of the studied drugs was within 80–120% in relation to the standard sample of semaglutide. The bioequivalence and a similar safety profile, including the immunogenicity and tolerability of the Russian drug Quincenta® (semaglutide 1.34 mg/ml, Promomed Rus LLC, Russia) were shown in comparison with the foreign drug Ozempic® (semaglutide 1.34 mg/ml, Novo Nordisk A/C, Denmark).